The Role of Internet Use on Individual Income: East Java Rural Case Study - M. Fahmi Priyatna; Sonia Anggun Andini (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
This study analyzes the role of internet utilization on individual income in rural areas of East Java and Peer Provinces (West Java and Central Java) using 2018 Sakernas data. This study uses propensity score matching (PSM) and a probit model to achieve the research objectives. The estimation results show that theprobability of using the internet in East Java is affected by individual age, working experience, formal and informal education, migration, financial management, and agricultural business. Furthermore, this study found that internet usage by individuals in rural areas of East Java Province has increased individual income.There is a difference in income between individuals using the internet and not using the internet, amounting to Rp263,400. When compared with Peer Province, the difference is still below Central Java and West Java, which respectively amounted to Rp323,325 and Rp283,357.